Perioperative Anaphylaxis to Chlorhexidine during Surgery and Septoplasty. (19th March 2017) - Teixeira de Abreu, Ana Paula; Ribeiro de Oliveira, Leonardo Ramos; Teixeira de Abreu, Ana Flavia; Ribeiro de Oliveira, Evandro; Santos de Melo Ireno, Michele; Aarestrup, Fernando Monteiro; Aarestrup, Matheus Fonseca; Aarestrup, Paula Fonseca
Abstract : Chlorhexidine is an antiseptic and disinfectant used in surgical and clinical practice since 1954 and is available in aqueous or alcoholic solutions 0.5%–4.0% and has a broad-spectrum activity. Despite their widespread use, allergic reactions with chlorhexidine are rarely reported. We describe a case of anaphylaxis with chlorhexidine during a septoplasty, turbinectomy, and maxillary sinusectomy. The patient presented with periorbital edema, hives, hypotension, and wheezing. Immediately after the diagnosis of anaphylaxis promethazine, hydrocortisone, and epinephrine were administered with immediate clinical improvement. This case highlights the importance of assessing whether there is a previous clinical history of hypersensitivity to chlorhexidine in patients who will undergo surgical procedures.